Perbedaan Hasil Belajar PPKn Pada Pembelajaran Luring Dan Daring Menggunakan Media Visual Kelas IV B SDN 60 Kota Bengkulu - Alda Meliniawati; Puspa Djuwita; Lukman Lukman (Universitas Bengkulu, 2021)
This study aims to determine the differences in learning outcomes of Pancasila and Citizenship Education by using visual media in Offline and Online Learning and to find out the differences in the implementation of offline and online learning. The research sample was grade IV B students at SDN 60 Bengkulu city consisting of 22 students divided into 11 offline students and 11 online students, the method used was quantitative, the data collection techniques was using tests and documents, the data analysis technique was using a test the statistics There are differences in learning outcomes with visual media Offline and Online Learning Class IV B, this is indicated by the t_count value of 2.49 which is greater than the t_table value at a significant level of 5% of 1.68. while the documentation to find out the difference between offline and online implementation for class IV B SDN 60 Bengkulu City is seen from the learning process with visual media. The results of the study concluded that there were significant differences in offline and online learning using visual media between experimental class I and experimental class II. The test showed the offline average score was 86 greater than online 79 and the documentation showed the offline learning process was more optimal than online.Keyword: learning outcomes, offline and online, pancasila and citizenship education